Epidemiological Study on Factor VII, Factor VIII and Fibrinogen in an Industrial Population: I. Baseline Data on the Relation to Age, Gender, Body-Weight, Smoking, Alcohol, Pill-Using, and Menopause - Balleisen, L; Bailey, J; Epping, P-H; Schulte, H; van de Loo, J (Thrombosis and Haemostasis, 1985)
The Münster Arteriosclerosis Study (MAS) is a prospective, longitudinal epidemiological study on an industrial population in Westfalia aimed to establishing clinical and laboratory data with possible relationship to cardiovascular events. The data presented here describe the baseline measurements of fibrinogen, factor VIIc and factor VIIIc from the recruitment of 2880 male and 1306 female persons and their relationship to age, gender, body-weight, smoking, alcohol, pill-using and menopause. The correlations were made by means of a multiple regression analysis. We found an increase of those coagulation factors with age, a correlation of F VII and fibrinogen with body-weight index and of fibrinogen with cigarette smoking. No correlation was found for alcohol consumption. F VIII and F VII were significantly higher after onset of menopause and F VII and fibrinogen in women using the pill.
Keywords: Factor VII; Factor VIII; Fibrinogen; Epidemiology